Social innovations in the company’s strategic goals: peculiarities, classification, efficiency evaluation - Vostriakov, Oleksandr; Notevskyi, Yevhenii (Technology audit and production reserves, 2023)
The article is devoted to the features, classification and evaluation of the effectiveness of social innovations in the implementation of the company's strategic goals. The object of the study is the process of formation and implementation of social innovations in the company's activities. At the same time, the development of the concept of social innovations from the 19th century to the present is considered in detail. Special attention is paid to the interpretation of social innovations and strategic goals of the company in Ukrainian and foreign economic science. The research problem is the complexity of forming modern classifications and evaluating the effectiveness of social innovations in the company's strategic goals. The essence of the obtained results is the disclosure of the theoretical provisions of social innovations and strategic goals, the determination of approaches and methods for evaluating the effectiveness of social innovations, as well as the role of social innovations as a tool for achieving the strategic goals of the enterprise. In the reasoned conclusions of the study, it is explained that the gradation of the results of the implementation of social innovations at the enterprise depending on the type (personal, economic, image and social) indicates that each of them has both positive and negative features; methods of evaluating the impact of innovations on the company's performance are shown. In particular, the assessment of the effectiveness of social innovations is also important because their implementation requires a lot additional efforts, which shifts the focus and can distract from solving important issues that are often urgent. The state of war, the destruction of the usual approaches to doing business, the loss of qualified management personnel, specialists in various processes does not allow to effectively find and implement innovations in the social, environmental and managerial components. All these aspects are considered in the context of the effective implementation of the company's strategic goals in the conditions of a dynamic transformational society, in which the research results can be used in practice.